HUBUNGAN POLA ASUH IBU DENGAN PERILAKU PICKY EATING PADA ANAK USIA PRASEKOLAH DI LINGKUNGAN VII SIMALINGKAR KELURAHAN MANGGA DUA KECAMATAN MEDAN TUNTUNGAN TAHUN 2019 - Hetty Simamora; Ance M Siallagan (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2020)
Picky eating is the behavior of children who experience eating disorders in the form of refusal to eat, do not want to eat, the length of time to eat more than 30 minutes, and only want to eat certain foods. The purpose of this study was to determine the relationship between maternal parenting with Picky Eating behavior in preschool children in Simalingkar VII Ward, Mangga Dua Village, Medan Tuntung District. This research uses correlation research design with cross sectional approach method. Population The population in this study were all preschool children (3-5 years old) in the VII Environment of Simalingkar, Mangga Dua Village, Medan Tuntung District, as many as 36 people and their mothers. Sampling in this study is a way to do with a total sampling technique in which all populations are sampled, where the number of respondents is equal to the total population of 36 respondents, namely mothers who have preschool age children in the Simalingkar District VII, Mangga Dua Village, Medan Tuntung District. The results of this study indicate that there is no relationship between maternal parenting and picky eating behavior in preschool children in Simalingkar Ward VII Mangga Dua, Medan Tuntung District. Suggested to the next researcher to review about other factors related to picky eating behavior in preschool children.